Cover Feature: Metallation‐Induced Heterogeneous Dynamics of DNA Revealed by Single‐Molecule FRET (Chem. Eur. J. 22/2020). Issue 22 (16th April 2020) - Berrocal‐Martin, Raul; Sanchez‐Cano, Carlos; Chiu, Cookson K. C.; Needham, Russell J.; Sadler, Peter J.; Magennis, Steven W.
Abstract : The metallation of a DNA hairpin by an organo‐osmium anticancer complex was studied using single‐molecule Förster resonance energy transfer (FRET) microscopy. Ensemble measurements suggested simple, two‐state opening and closing of the hairpin, while single‐molecule experiments revealed complex DNA dynamics which are attributed to different degrees of metallation of the GC‐rich hairpin stem. More information can be found in the Full Paper by P. J. Sadler, S. W. Magennis, et al. on page 4980 .